Nurses’ Role in Preventing Delays in Escalation of Care in Hospitalized Patients - Riyad Judaya Funtul Alruwaili; Jamilah Ayed Alruwaili; Nouf Nazzal R Al Hazmi; Mubarak Awadh Khunaifer Alrashidi; Intisar Saeed Kassab Alshammary; Falha Saadi Hamoud Alshammari; Hamda Ateeq Alshammari; Jamilah Munawikh Jawban Alkuwaykibi; Gharam Feza Faleh Alhazmi; Matlak Falah Matlak Alotaibi; et al. (International Journal of Computational and Experimental Science and Engineering, 2024)
The nurse serves as the pivotal frontline defender against delays in escalating care for hospitalized patients, acting through a multifaceted role that integrates continuous surveillance, astute clinical judgment, and assertive advocacy. By employing structured assessment tools like Early Warning Scores alongside expert intuition, nurses are uniquely positioned to detect subtle signs of clinical deterioration early. They then bridge the critical communication gap to physicians by utilizing standardized frameworks like SBAR (Situation, Background, Assessment, Recommendation), ensuring concerns are conveyed clearly and urgently. Beyond communication, nurses must persistently advocate for their patients, navigating hierarchical barriers and systemic challenges to ensure an appropriate response. This role is further enhanced by educating and empowering patients and families to voice concerns, thereby creating an additional safety net. Ultimately, the nurse’s effectiveness in preventing escalation delays is a fundamental determinant of patient safety, directly impacting outcomes such as unplanned ICU admissions, cardiac arrests, and mortality, underscoring the need for supportive staffing, a culture of psychological safety, and ongoing interprofessional collaboration.